Comprehensive Analysis of Speech Deficits after Dominant Hemisphere Glioma Surgery having Integrated Exoscopic Neuronavigation, fMRI and DTI at Punjab Institute of Neurosciences, Lahore - Noman, Hamza; Adeeb Ul Hassan; Nawaz, Bakht; Hussain Shah, Syed Shahzad; Kamboh, Usman Ahmed; Bhutta, Muhammad Ubaid ur Rehman (Indus Journal of Bioscience Research, 2025)
Background: The surgery for gliomas involves resection of as much tumour as possible without causing neurological deficit. Speech is one of the modalities most at risk of impairment in these surgeries especially around perisylvian cortices. With modalities such as fMRI, DTI and exoscopic neuronavigation, we can hope to reduce these impairments to a minimum. Objectives: 1. To determine the frequency of speech deficits in post operative patients of dominant hemisphere gliomas using the quick aphasia battery.2.To assess the benefits of functional MRI, Diffusion tensor imaging tractography and exoscopic neuro-navigation in surgery of these patients.Materials & Method: In this study, a cohort comprising 60 patients was analysed. Data collection spanned from February 2025 to May 15, 2025. Prior to surgical intervention, all patients underwent comprehensive preoperative imaging assessments – fMRI, DTI and neuronavigation protocol MRIs. To evaluate speech, assessments were performed on all patients both before and after surgery using the Quick aphasia battery (QAB) – a validated scale for speech assessment, with follow-up evaluations conducted at 1 month postoperatively. The speech impairments were correlated with factors such as size and location of tumour. Results: Preoperatively, all 60 patients exhibited intact neurological function. However, in the postoperative phase, 33 patients experienced speech impairments. Notably, these deficits exhibited an encouraging trend toward gradual improvement, ultimately reaching a state of normalcy in many patients (20/33) over a span of 1 month. Glioma location and glioma size were variables significantly associated with frequency of speech deficits. Conclusion: Our findings highlight the significance of using these advanced modalities in management of dominant hemisphere gliomas and what to expect in terms of speech deficits with respect to the size and location of tumours.